A Triple High Throughput Screening for Extracellular Vesicle Inducing Agents With Immunostimulatory Activity - Shukla, Nikunj M.; Sato-Kaneko, Fumi; Yao, Shiyin; Pu, Minya; Chan, Michael; Lao, Fitzgerald S.; Sako, Yukiya; Saito, Tetsuya; Messer, Karen; Hayashi, Tomoko; Cottam, Howard B.; Corr, Maripat; et al. (Frontiers in Pharmacology, 2022)
Extracellular vesicles (EVs) play an important role in intercellular communication and regulation of cells, especially in the immune system where EVs can participate in antigen presentation and may have adjuvant effects. We aimed to identify small molecule compounds that can increase EV release and thereby enhance the immunogenicity of vaccines. We utilized a THP-1 reporter cell line engineered to release EV-associated tetraspanin (CD63)-Turbo-luciferase to quantitatively measure EVs released in culture supernatants as a readout of a high throughput screen (HTS) of 27,895 compounds. In parallel, the cytotoxicity of the compounds was evaluated by PrestoBlue dye assay. For screening immunostimulatory potency, we performed two additional independent HTS on the same compound library using NF-κB and interferon-stimulated response element THP-1 reporter cell lines. Hit compounds were then identified in each of the 3 HTS’s, using a “Top X” and a Gaussian Mixture Model approach to rule out false positive compounds and to increase the sensitivity of the hit selection. Thus, 644 compounds were selected as hits which were further evaluated for induction of IL-12 in murine bone-marrow derived dendritic cells (mBMDCs) and for effects of cell viability. The resulting 130 hits were then assessed from a medicinal chemistry perspective to remove compounds with functional group liabilities. Finally, 80 compounds were evaluated as vaccine adjuvants in vivo using ovalbumin as a model antigen. We analyzed 18 compounds with adjuvant activity for their ability to induce the expression of co-stimulatory molecules on mBMDCs. The full complement of data was then used to cluster the compounds into 4 distinct biological activity profiles. These compounds were also evaluated for quantitation of EV release and spider plot overlays were generated to compare the activity profiles of compounds within each cluster. This tiered screening process identified two compounds that belong to the 4-thieno-2-thiopyrimidine scaffold with identical screening profiles supporting data reproducibility and validating the overall screening process. Correlation patterns in the adjuvanticity data suggested a role for CD63 and NF-κB pathways in potentiating antigen-specific antibody production. Thus, our three independent cell-based HTS campaigns led to identification of immunostimulatory compounds that release EVs and have adjuvant activity.